Implementation of Primary School Students' Religious Character Through School Culture - Bela, Dinda Velita; Santosa, Achadi Budi (Universitas Islam Sultan Agung, 2023)
Abstract This research was conducted to reveal the embodiment of religious character education through school culture. Through a qualitative approach, the case study model of this research uses school principals and teachers as the main respondents. Data collection techniques use interviews and field observations. The collected data was analyzed using the Miles & Huberman model, and its validity was tested using source triangulation and technical triangulation. The results of the research show that religious character education is formed 1) in the habit of congregational prayer, such as Duha prayers, prayers before and after learning, 2) in the form of physical objects, artifacts that have a religious pattern and religious value. All buildings and physical objects are used to strengthen an environment that supports a religious character. 3) a culture of thinking which is manifested in the vision and mission of the Islamic boarding school, the religious thoughts of students and teachers which are expressed in their behavior and spirit of faith. The culture of ideas is realized in everyday life. Its implementation is supported by factors such as adequate capacity and participation of all school children in school culture. The inhibiting factor is a lack of awareness among some students and differences in ability.